Sound source localization using hearing aids with microphones placed behind-the-ear, in-the-canal, and in-the-pinna - Van den Bogaert, Tim; Carette, Evelyne; Wouters, Jan (International journal of audiology, 2011)
The effect of different commercial hearing aids on the ability to resolve front-back confusions and on sound localization in the frontal horizontal and vertical plane was studied. Commercial hearing aids with a microphone placed in-the-ear-canal (ITC), behind-the-ear (BTE), and in-the-pinna (ITP) were evaluated in the frontal and full horizontal plane, and in the frontal vertical plane. A group of 13 hearing-impaired subjects evaluated the hearing aids. Nine normal-hearing listeners were used as a reference group. Differences in sound localization in the front-back dimension were found for different hearing aids. A large inter-subject variability was found during the front-back and elevation experiments. With ITP or ITC microphones, almost all natural spectral information was preserved. One of the BTE hearing aids, which is equipped with a directional microphone configuration, generated a sufficient amount of spectral cues to allow front-back discrimination. No significant effect of hearing aids on elevation performance in the frontal vertical plane was observed. Hearing-impaired subjects reached the same performance with and without the different hearing aids. In the unaided condition, a frequency-specific audibility correction was applied. Some of the hearing-impaired listeners reached normal hearing performance with this correction.